Report of the Rajasthan-Madya Bharat Jagir Enquiry Committee - Planning Commission (Planning Commission, 1950)
The Rajasthan-Madhya Bharat Jagir Enquiry Committee Report (1949) examines the historical Jagirdari and Zamindari systems, highlighting their dominance by intermediaries and the challenges faced by tenants in Rajasthan and Madhya Bharat. The committee identified inefficiencies in land records, inequitable tenant rights, and resistance to reform, emphasizing the need for direct governance between cultivators and the state. Key recommendations include the abolition of Jagir and Zamindari systems, establishment of clear land tenure frameworks, tenant protection, phased compensation for former intermediaries, and streamlined land revenue administration. The report advocates for a unified tenure system, equitable land distribution, and interim measures to safeguard tenant livelihoods, aiming to modernize agriculture and promote social and economic justice in the region.
Planning Commission
Planning Commission
Keywords: Rajasthan; Madhya Bharat; Jagir; Zamindari; Tenancy; Land Reforms; Tenant Rights; Land Revenue; Abolition; Agricultural Administration